Redecoration of apartments promotes obstructive bronchitis in atopy risk infants – Results of the LARS study - Diez, Ulrike (Int J Hyg Environ Health, 2003)
Findings by other authors indicate that exposure to chemical emissions from indoor paint is related to asthma symptoms in adults. In their first years of life children are receptive to obstructive airway diseases. The aim of this study was to investigate the influence of redecoration of the apartment on airway symptoms in infants during the first two years of life. The Leipzig Allergy Risk Children Study (LARS) is a birth cohort study with the following inclusion criteria: double positive family atopy anamnesis, cord blood IgE>0.9 kU/l, or low birth weight between 1500 – 2500 g. Within the context of LARS, 186 parents of risk children completed a questionnaire on the respiratory symptoms of their children and the redecoration of their apartment at the end of the first and second year of life. A total 22% of the children suffered from obstructive bronchitis once or more during their first year, and 11% experienced this condition during their second year of life. Redecoration of the apartment had a significant influence on the appearance of obstructive bronchitis in the first (OR 4.1 95%CI 1.4 – 11.9) and in the second year of life (OR 4.2 95%CI 1.4 – 12.9). (The OR are adjusted for cord blood-IgE >0.9 kU/l, birth weight ≤2500 g, male sex and double positive parental atopy anamnesis, dampness, smoking or pet in the apartment). Simultaneous contamination from redecoration activities and additional exposures such as smoking, a pet or dampness in the apartment increased the risk for obstructive bronchitis in the first year (OR 9.1; 95% CI 2.3 – 34.8) as well as in the second year (OR 5.1; 95%CI 1.6 – 15.6). Our data suggest that redecoration of the apartment is associated with the development of acute inflammations, but not with a chronic influence on the airways in atopy risk infants. At an exposure to more than one environmental factor, pronounced effects were seen.